Organellar genome copy number variations and integrity across different organs, growth stages, phenotypes and main localities of sago palm (Metroxylon sagu Rottboll) in Sarawak, Malaysia - Whye, Leonard Kit Lim; Chung, Hung Hui; Hasnain, Hussain (Elsevier, 2020)
The sago palm (Metroxylon sagu Rottboll) is one valuable food crop that has both high economic and nature value with promising potential to curb future global hunger issues. The organellar genomes, namely mitogenome and plastome, are indispensable in various development processes of plants, orchestrating the survivability and adaptability of the host and fulfilling its physiological needs. The long-PCR and qPCR approaches were used in couple to reveal the organellar genome copy number variations across different organs, growth stages, phenotypes and main localities in Sarawak, Malaysia. In this study, the mature leaf achieved among the highest unimpeded plastome and mitogenome copy number among other organs such as young root, mature root, young shoot, aged leaf and pneumatophore. The Plawei Manit stage scored the highest in terms of unimpeded mitogenome and plastome copy number across other four growth stages. The non-trunking and spiny phenotypes inspected have lower organellar genome copy numbers than the trunking phenotype. All three phenotypes sampled from four different localities in Sarawak, Malaysia showed no significant difference. This study serves as a steppingstone in unravelling the organellar genome copy number variations of sago palm and this knowledge is essential for future genotyping studies.